Large anomalous Hall effect in the chiral-lattice antiferromagnet CoNb3S6 - Nirmal J. Ghimire; A. S. Botana; J. S. Jiang; Junjie Zhang; Y.-S. Chen; J. F. Mitchell (Nature Communications, 2018)
Anomalous Hall effect (AHE) in antiferromagnets is intriguing and requires further understanding. Here the authors report large AHE in a chiral-lattice antiferromagnet CoNb3S6 of which the origin can be due to complex magnetic texture or broken time-reversal symmetry on the electronic band structure.